Molecular Phylogenetic Exploration of Bacterial Diversity in a Bakreshwar (India) Hot Spring and Culture of Shewanella-Related Thermophiles - Ghosh, Dhritiman (American Society for Microbiology, 2003)
The bacterial diversity of a hot spring in Bakreshwar, India, was investigated by a culture-independent approach. 16S ribosomal DNA clones derived from the sediment samples were found to be associated with gamma-Proteobacteria, cyanobacteria, and green nonsulfur and low-GC gram-positive bacteria. The first of the above phylotypes cobranches with Shewanella, a well-known iron reducer. This phylogenetic correlation has been exploited to develop culture conditions for thermophilic iron-reducing microorganisms.